The Stigma System: How sociopolitical domination, scapegoating and stigma shape public health - Friedman, Samuel (2021)
Stigma is a fundamental driver of adverse health outcomes. Although stigma is often studied at the individual level to focus on how stigma influences the mental and physical health of the stigmatized, considerable research has shown that stigma is multilevel and structural. This paper proposes a theoretical approach that synthesizes the literature on stigma with the literature on scapegoating and divide-and-rule as strategies that the wealthy and powerful use to maintain their power and wealth; the literatures on racial, gender, and other subordination; the literature on ideology and organization in sociopolitical systems; and the literature on resistance and rebellion against stigma, oppression and other forms of subordination. we develop a model of the ?stigma system? as a dialectic of interacting and conflicting structures and processes. Understanding this system can help public health re-orient stigma interventions to address the sources of stigma as well as the individual problems that stigma creates. On a broader level, this model can help those opposing stigma and its effects to develop alliances and strategies with which to oppose stigma and the processes that create it.